The Berenstain Bears' let's talk about money - Berenstain, Stan, 1923-2005; Berenstain, Jan, 1923-2012 (New York : Random House, 2023)
"Help children learn about money with this storybook featuring two bestselling Berenstain Bears stories in one book! Featuring The Berenstain Bears Trouble with Money and The Berenstain Bears Dollars and Sense, this full-color storybook is the perfect addition to your Berenstain Bears collection! The Berenstain Bears Trouble with Money: Mama and Papa are worried that Brother and Sister seem to think money grows on trees. To make money of their own, the cubs decide to start their very own businesses, from a lemonade stand to a pet-walking service! The Berenstain Bears Dollars and Sense: Papa thinks it's time to teach Brother and Sister how to budget their money, but will the cubs come to understand the value of a dollar, or will their pockets continue to be empty?" -- ONIX annotation.
The Berenstain Bears' trouble with money -- The Berenstain Bears' dollars and sense.
"2 books in 1!"--Cover.
"The Berenstain Bears' Classics"--Cover.
The stories in this collection were originally published separately in the United States by Random House Children's Books in 1983 and 1991.
Keywords: Berenstain Bears (Fictitious characters) -- Juvenile fiction; Bears -- Juvenile fiction; Money -- Juvenile fiction; Finance, Personal -- Juvenile fiction; Moneymaking projects -- Juvenile fiction; Picture books